Traditional Defensive Landscapes as Traces of Past Conflicts in Toraya: An Approach to Conflict Archaeology and Collective Memory - Benyamin Lufpi (Eduvest - Journal of Universal Studies, 2026)
Traditional defensive landscapes in Toraja, South Sulawesi, represent important archaeological traces of past conflict, yet they have received limited attention within Indonesian conflict archaeology. This study aimed to examine how traditional defense sites in Toraja reflect historical conflict, environmental adaptation, and collective memory. The research employed a qualitative approach by integrating archaeological survey, documentation of defensive structures, landscape mapping, semi-structured interviews with local informants, and analysis of archival and historical sources. The study focused on four main sites: Ka'do To'ria Fort, Tangdi Rompo Silanan Fort, Buntu Pune, and Batu Tengan/Kandora Hill. The findings showed that these sites utilized mountainous topography, karst hills, vertical cliffs, narrow access routes, stone walls, wells, surveillance points, and defensive vegetation as strategic elements of protection. The remains indicate responses to intergroup conflict, regional political pressure, and Dutch colonial expansion. The discussion also revealed that oral traditions concerning Pongtiku, To Barani, and territorial defense continue to preserve these sites as symbols of identity, resistance, and communal memory. In conclusion, Toraja’s traditional defensive landscapes are not merely physical remnants of warfare, but integrated cultural landscapes that connect material evidence, spatial strategy, and collective memory. This study contributes to conflict archaeology and supports community-based heritage preservation in Toraja.